Analisis Kontribusi Tafsir Tarbawi Terhadap Pengembangan Pendidikan Kritis dan Analitis - Mirza, Iskandar; Wijaya, Andri (Penerbit Widina, Widina Media Utama, 2025)
In the context of Islamic education, tafsir tarbawi plays an important role in enhancing critical and analytical education. Tafsir tarbawi, which means